2019
DOI: 10.3390/jpm9010002
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR4 Polymorphisms, Expression, and Vitamin D with Helicobacter pylori Infection

Abstract: Helicobacter pylori (H. pylori) infection is the strongest recognized risk factor for gastric adenocarcinoma. Since previous observations have shown that polymorphisms in innate immune system genes, as well as vitamin D (VitD) levels, could modify the risk of infection with Helicobacter pylori (H. pylori), we analyzed the relation between single nucleotide polymorphisms (SNPs) in TLRs (TLR1, TLR2, TLR4) CD14, RUNX3 and VitD levels with H. pylori infection. A case-control study on four hundred sixty Lebanese in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Our search identified 182 related references, of which 10 papers met our inclusion criteria . The flowchart describing the process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified 182 related references, of which 10 papers met our inclusion criteria . The flowchart describing the process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Participants involved in the present study were recruited in accordance with the latest version of the Declaration of Helsinki for Ethical Principles for Medical Research Involving Human Subjects as described previously [13]. Protocols for the genetic studies were approved by the local ethics committees for the protection of subjects for biomedical research.…”
Section: Methodsmentioning
confidence: 99%
“…All measurements, including demographic, clinical, and biochemical measurements, were assessed as described previously [11]. Nuclear DNA was extracted from whole-blood samples according to the manufacturer's recommendations (QIAamp DNA blood mini kit, Qiagen, Hilden, Germany).…”
Section: Clinical and Biological Data Collectionmentioning
confidence: 99%